Agrivoltaic: A strategic assessment using SWOT and TOWS matrix - Maity, Rittick; Sudhakar, K.; Amir, Abdul Razak; Karthick, A.; Barbulescu, Dan (MDPI AG, 2023)
New strategies and market segments considering integrated approaches have emerged as critical components in the energy transition. Agrivoltaics is one approach that has shown a lot of promise for offering advantages in the food-energy-water nexus. The agrivoltaic system involves the installation of photovoltaic panels above agricultural lands to generate electricity while also allowing for crop production. The paper “SWOT and TOWS Matrix Analysis of Agrivoltaic System” comprehensively analyses the potential strengths, weaknesses, opportunities, and threats (SWOT) associated with implementing an agrivoltaic system. This study utilizes a SWOT analysis framework to identify and evaluate the internal and external factors that could impact the implementation and success of the agrivoltaic system. A TOWS matrix analysis is also conducted to formulate strategic recommendations based on the identified SWOT factors. The analysis results reveal that the agrivoltaic system has numerous strengths, including its potential to generate renewable energy, increase crop yield, and provide economic benefits to farmers. However, the system also faces several weaknesses and threats, such as high initial investment costs, land use conflicts, and potential environmental impacts. Based on the TOWS matrix analysis, this study provides strategic recommendations to maximize the potential of the agrivoltaic system while mitigating its weaknesses and threats. These recommendations include adopting a flexible pricing strategy, researching the system’s environmental impact, promoting collaboration between various stakeholders like government agencies, farmers, and energy service companies. Overall, this study provides valuable insights into the potential of agrivoltaic systems and the factors that should be considered when implementing such a system. The findings can help stakeholders make informed decisions and take appropriate actions to ensure the integration of agrivoltaic systems into agricultural practices.